Evaluating the Impact of a University Pharmacy Vending Machine Program - Haley M. Sidorowicz; Alexandra T. Hughes-Wegner; Anna G. Trieloff; Sophia P. Patel; Jaslin A. Martinez; Katie R. Figliomeni; Rhea C. Shah; Nicole Noel; Andrea L. DeMaria (New Prairie Press, 2024)
This study assesses the impact and potential enhancements of a Pharmacy Vending Machine (PhVM) program implemented at Purdue University since January 2021. Aimed at addressing the accessibility gap for essential healthcare items, particularly sexual and reproductive health products, and over-the-counter medications, the program has expanded from two to eight PhVMs on campus. A web-based survey was completed by a random University sample (n=469) to evaluate the program's efficacy and identify avenues for improvement. Survey responses and sales data from January 2021 to April 2023 were analyzed. Findings demonstrate a positive reception of the PhVMs, highlighting a preference for increased accessibility to sexual and reproductive healthcare items. Word-of-mouth remains a key source of awareness for vending machines, suggesting the significance of targeted marketing strategies and information dissemination within on-campus groups. Sales data trends underscore the necessity for ongoing assessment to optimize student access to PhVMs. This study is a comprehensive evaluation, emphasizing the importance of continual refinement in healthcare vending initiatives to cater effectively to campus community needs.